2014
DOI: 10.1002/hep.26767
|View full text |Cite
|
Sign up to set email alerts
|

Association between thePNPLA3(rs738409 C>G) variant and hepatocellular carcinoma: Evidence from a meta-analysis of individual participant data

Abstract: The incidence of hepatocellular carcinoma (HCC) is increasing in Western countries. Although several clinical factors have been identified, many individuals never develop HCC, suggesting a genetic susceptibility. However, to date, only a few single-nucleotide polymorphisms have been reproducibly shown to be linked to HCC onset. A variant (rs738409 C>G, encoding for p.I148M) in the PNPLA3 gene is associated with liver damage in chronic liver diseases. Interestingly, several studies have reported that the minor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
144
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(161 citation statements)
references
References 43 publications
10
144
2
5
Order By: Relevance
“…A recent meta-analysis of individual patient data from candidate gene studies has shown that the PNPLA3 rs738409 G allele is also an independent risk factor for the development of HCC in this patient population [10,11]. Recently, variants in two further genes viz.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of individual patient data from candidate gene studies has shown that the PNPLA3 rs738409 G allele is also an independent risk factor for the development of HCC in this patient population [10,11]. Recently, variants in two further genes viz.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its strong influence on hepatic steatosis of various etiologies, a significant association between PNPLA3 polymorphism and the development of HCC has been consistently found only among patients with fatty liver diseases, including ASH and NASH (Trepo et al, 2012;Guyot et al, 2013;Takeuchi et al, 2013;Liu et al, 2014;Trepo et al, 2014). Indeed, both ASH and NASH have rather similar disease spectrums, starting with fatty liver change followed by inflammation, progressive fibrosis, and finally cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, only two small-sample case-control studies from Italy [32,61] initially reported a positive association between rs738409[G] and HCC in HCV-infected patients, while at least 2 others did not observe this result [55,56]. Moreover, results obtained from meta-analyses of these studies did not provide firm conclusions [16,53]. Finally, the American multicentric HALT-C trial did not observe a higher risk of liver cancer occurrence in individuals carrying the rs738409[G] allele [62].…”
Section: Pnpla3 and Hepatocellular Carcinomamentioning
confidence: 98%
“…These initial reports identified a significant association between rs738409[G] and HCC. However, although the results seem concordant for individuals of European descent with non-viral HCC, they remain conflicting in HCV-infected patients [53]. Table 2 shows reported positive associations according to etiology of liver disease and highlights the limitations or quality criteria allowing a critical assessment of these studies.…”
Section: Pnpla3 and Hepatocellular Carcinomamentioning
confidence: 98%
See 1 more Smart Citation